Issues of Accounting Presentation of Metals and Mining Companies at Key Exploration Work Stages - A. S. Mal’tsev (Учёт. Анализ. Аудит)
The paper provides an overview of the main stages and types of exploration works for solid minerals according to the current regulatory documents of the Ministry of Natural Resources and Ecology of the Russian Federation, and also considers the features of accounting for these works in conformity with the requirements of RAS 24/2011 “Accounting for the costs on exploitation of natural resources”, IFRS 6 “Exploration and Assessment of Mineral Reserves” and IAS 36 “Asset Impairment”. According to the results of a comparative analysis of RAS and IFRS, assessment of the methods for reflecting exploration work in the accounting of mining companies, an analysis of their impact on management decisions by stakeholders is carried out. The theoretical and practical significance of the study is to justify the need to develop an alternative methodology for accounting and presentation of accounting information on the results of exploration, based on a phased increase in the reliability of knowledge about subsoil areas. The study is primarily interest to government agencies for improving the legislative regulation of accounting, credit institutions and mining companies in conducting investment analysis of customers and partners.